Aerial sonic anemometry - preleminary results - Marques, Filipe (2014)
ASA (Aerial Sonic Anemometry) project intends to use sonic anemometers in airborne platforms, complementing meteorological masts measurements over mountainous terrain. The additional information will be inputted into CFD models to assess complex mean and turbulent flow fields over mountainous terrain for wind energy purposes. The kind of platform and its distortion over the sonic measuring volume was considered: sonic anemometer structure over the platform and its behavior, and sonic transducers location relatively to platform. These limitations conditioned the choice of model planes to units with central or rear plan propulsion. Due to the lack of commercial offer, this type of configuration combined with payload capacity, led our choice to the Hobbyking FPV 168 with a wingspan of 1660 mm, fuselage of 1190 mm and a payload capacity of 2.3 kg. To prevent the distortion on the measurement volume, the minimal distance from the sonic head to the plane model was set to be equal to the distance from the front to the wing’s leading edge. The concept of flying a model plane with a sonic anemometer installed on it was validated, and it was possible to fly the model hauling a proxy of a Young 81000 sonic anemometer with perfect flying control. Flying tests were made in order to establish the best configuration of the center of mass of whole setup: airframe, batteries and sonic proxy structure. An electrical engine was used for commodity. The plane equipped with a 10”x7” 3 bladed pusher propeller, and at maximum engine rotation and local atmospheric conditions the batteries yielded a maximum of 37 Ah for the whole electric system. The flight autonomy is estimated to be between 8 to 10 minutes depending on local winds (1 battery of 4 elements of 4.2 V and 3700mAh). Future steps of this project are the use of the present setup to explore GPS, autopilot and data acquisition features. The increase of flight autonomy with the sonic platform will require larger aircrafts that are undergoing a process of selection.